2009
DOI: 10.1177/1069072709334237
|View full text |Cite
|
Sign up to set email alerts
|

Development and Criterion Validity of Differentiated and Elevated Vocational Interests in Adolescence

Abstract: Interest differentiation and elevation are supposed to provide important information about a person's state of interest development yet little is known about their development and criterion validity. The present study explored these constructs among a group of Swiss adolescents. Study 1 applied a cross-sectional design with 210 students in eleventh grade. Study 2 applied a one-year longitudinal design with 289 students in seventh to eighth grade. Gender, personality traits, and career exploration were signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 37 publications
1
26
0
6
Order By: Relevance
“…The result is in line with previous studies (Fouad & Mohler, 2004;Hirschi, 2009;Stark, 2001) which found that female students had a higher level of differentiation career interest than male students. According to Hirschi and Läge (2008), female students have a higher level of interest differentiation because they are generally more knowledgeable and have more information about the career world than male students.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The result is in line with previous studies (Fouad & Mohler, 2004;Hirschi, 2009;Stark, 2001) which found that female students had a higher level of differentiation career interest than male students. According to Hirschi and Läge (2008), female students have a higher level of interest differentiation because they are generally more knowledgeable and have more information about the career world than male students.…”
Section: Discussionsupporting
confidence: 93%
“…A clear career interest makes it easier for an individual to determine career decisions and career plans (Donohue, 2006;Hirschi & Läge, 2008;Hirschi & Läge, 2007;Hirschi, 2009;Nauta, 2005;Davis, 2007). Some other researchers have reported that students who have clear career interests obviously also have a high level of confidence in achieving a higher level of education (Nauta, 2007;Hirschi & Läge, 2007;Davis, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…More differentiated interest profiles are related to positive career outcomes such as career choice readiness and vocational identity (Hirschi & Läge, ) and more stable career aspirations (Bergmann, ). Research within Holland's () RIASEC framework further indicates that women tend to have more differentiated interest profiles than men in middle school, high school, and college (Fouad & Mohler, ; Hirschi, ; Tracey & Robbins, ). However, research with mathematically gifted students found that male high school and college students had more differentiated interest and ability profiles than female students (Achter, Lubinski, Benbow, & Eftekhari‐Sanjani, ; Lubinski, Webb, Morelock, & Benbow, ).…”
mentioning
confidence: 99%
“…Quanto maior o valor, maior o nível de nitidez. Outra forma de obter esse índice é a partir do desvio padrão de todas as dimensões (Hirschi, 2009). Ao verificar que a correlação entre os dois métodos foi de 0,975, optou-se por utilizar nas análises deste estudo a maneira tradicional, sugerida por Holland (1997).…”
Section: Análise De Dadosunclassified
“…Algumas pesquisas realizadas no contexto internacional empregaram delineamentos longitudinais ou de teste--reteste a fim de verificar a estabilidade das medidas de interesses profissionais (Lent, Tracey, Brown, Soresi, & Nota, 2006;Primé & Tracey, 2010;Rottinghaus, Coon, Gaffey, & Zytowski, 2007) e explorar a utilidade dos conceitos secundários (Hirschi, 2009(Hirschi, , 2010. Hirschi (2010) fez duas aplicações de um instrumento baseado no modelo tipológico de Holland (1997) em uma amostra composta por adolescentes, com intervalo de dez meses.…”
unclassified